US campus fraternities and sororities and the young adult injury burden. Issue 5 (4th July 2018) - Peterson, Cora; Foster, Stephanie L.; Xu, Likang; Hartnett, William M.; Florence, Curtis; Haileyesus, Tadesse
ABSTRACT: Objective : To investigate whether the presence of fraternities and sororities was associated with a higher local injury rate among undergraduate-age youth.Methods : In 2016 we compared the rate of 2010–2013 youth (18–24 years) emergency department (ED) visits for injuries in Hospital Service Areas (HSA) with and without fraternities and sororities. ED visits were identified in the State Emergency Department Database (n=1, 560 hospitals, 1, 080 HSAs, 16 states). US Census Bureau and National Center for Education Statistics sources identified HSA population and campus (n=659) characteristics. A proprietary database identified campuses with fraternities and sororities (n=287). ED visits explicitly linked to fraternities and sororities in the National Electronic Injury Surveillance System–All Injury Program were used to identify injury causes for sub-group analysis.Results : HSAs serving campuses with fraternities and sororities had lower age 18–24 injury rates for all causes except firearm injuries (no difference).Conclusions : Fraternities and sororities were not associated with a higher injury rate at the population level among undergraduate-age youth. A major limitation is not being able to observe campus health services utilization.